Ouvindo vazios : os silêncios em A erva do rato e Cleópatra de Júlio Bressane - Terezani, João Henrique Tellaroli (2014)
This work aims to discuss the representation of silence in films. Our objects of study are the films Cleópatra and A erva do rato both by Julio Bressane, since the phenomenon of silence emerges as a recurring theme in the style of this director. The analyzes found in this work focus on the discussion of the phenomenon linked to its discursive, and its physical appearance, and also about its manifestations in artistic fields like music, poetry and cinema. To do so, we had as main references studies of Paul Théberge, Fernando Morais da Costa, Virginia Flores about the sound in cinema, John Cage, Susan Sontag, José Miguel and Jorge Antunes Wisnik on the representativeness of silence for the arts in general.